Study of mechanisms bonding in the binary boron compounds crystallized in structural type AlB2 - Aslan, Asem; Mahmoud, Kinda (Latakia University Journal -Basic Sciences Series, 2018)
The present study aims primarily to interprete the correlation in a large array of metal compounds of Boron element, We have adopted the method of discussion and analysis in the study of the quality and correlation mechanism of the structural model AlB2 , Away from traditional concepts that were often unable to explain the bonding in these compounds . The results can be useful scientific and reference ; We can rely on them as a basis for studying similar structural models and explain the bonding in them.